Evaluation of an endotracheal intubation model and practical for training veterinary nursing students. Issue 2 (1st February 2020) - Harris, Rachel; O'Reilly, Maire; Baillie, Sarah
Abstract : ABSTRACT: Endotracheal intubation practice, using a modified model dog was introduced to help student veterinary nurses prepare for anaesthetic procedures during clinical work-placements. The model was reviewed by five clinical experts who rated it as reasonably realistic and suitable for teaching and suggested minor improvements. Training was delivered to a cohort of students and their feedback was positive; they found the model helpful and had enjoyed the practical. A focus group and interviews were undertaken with some students after placements; they considered the practical had helped them prepare for and perform the task but requested additional opportunities to use the model.